Effects of a New Nano-Silver Fluoride-Containing Dentifrice on Demineralization of Enamel and Streptococcus mutans Adhesion and Acidogenicity - Joás Araújo Teixeira; Amitis Vieira Costa e Silva; Valdeci Elias dos Santos Júnior; Paulo Correia de Melo Júnior; Manuela Arnaud; Maria Goretti Lima; Miguel Angel Pelagio Flores; Thayza Christina Montenegro Stamford; José Ricardo Dias Pereira; Andréa Gadelha Ribeiro Targino; André Galembeck; Aronita Rosenblatt (International Journal of Dentistry)
An experimental dentifrice containing nano-silver fluoride (NSF) and a sodium fluoride (NaF) toothpaste were tested in vitro, against S. mutans, to evaluate the minimal inhibitory concentration (MIC), minimal bactericidal concentration (MBC), antiadherence, antiacid, enamel microhardness, and OCT. The microdilution technique was used to determine the MIC and MBC. Fragments of deciduous enamel were treated with dentifrice slurries, containing bacterial suspension and PBS-treated saliva. The quantification of the microorganisms that adhered to the enamel was determined after 24 hours of incubation, and media pH readings were performed after 2 hours and 24 hours. Deciduous teeth were evaluated for microhardness and OCT during 14 days of pH cycling. Data were statistically analyzed using Student’s t-test, Mann–Whitney U test, ANOVA, and Tukey tests at 5% of significance. Dentifrices containing NSF presented a lower MIC and higher statistically significant results compared to NaF dentifrices with respect to preventing bacterial adhesion and pH decreases. NSF and NaF dentifrices showed the same ability to avoid enamel demineralization corroborated by the OCT images. The NSF formulation had a better antibacterial effect compared to NaF dentifrices and similar action on the demineralization of enamel indicating their potential effectiveness to prevent caries.